2002
DOI: 10.1001/jama.288.22.2836
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Care Management of Late-Life Depression in the Primary Care Setting

Abstract: The IMPACT collaborative care model appears to be feasible and significantly more effective than usual care for depression in a wide range of primary care practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
1,707
4
26

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 2,161 publications
(1,800 citation statements)
references
References 75 publications
37
1,707
4
26
Order By: Relevance
“…This rate closely approximates retention in collaborative care research trials. (1, 3, 4, 27) Moreover, our survival models accounted for attrition in constructing estimates of outcomes over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate closely approximates retention in collaborative care research trials. (1, 3, 4, 27) Moreover, our survival models accounted for attrition in constructing estimates of outcomes over time.…”
Section: Discussionmentioning
confidence: 99%
“…(16) The IMPACT trial, one exemplar of collaborative care, demonstrated significant improvement in depression outcomes among elderly patients with cost savings in the long-term. (3) These promising results have engendered considerable national interest in the dissemination of integrated models, and the corresponding need to understand how to implement such models in real-world settings. (7, 8) Presently, little is known about the care provided or the outcomes achieved when such models are adopted by community-based practices, particularly those in resource-poor settings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, only 40-50% of older adults respond to the first prescribed antidepressant medication. 24-25 In those that do respond, response is often slow, sometimes taking up to 4 months 26 and once response is achieved, relapse and recurrence are common. Approximately 60% of community-dwelling older adults with MDD who initially responded to antidepressant treatment became depressed again within 2 years unless they were maintained on antidepressant pharmacotherapy.…”
Section: Late-life Depression: Definition Extent Burden and Hopementioning
confidence: 99%
“…82 Organized follow-up programs that include patient education, telephone or in-person contact every 2 to 4 weeks, monitoring of medication adherence, and psychiatric consultation as necessary improve outcomes for depressed cardiac patients. [83][84][85][86] "Measurement-based care," which uses frequent ratings of symptoms and adverse effects to guide dose adjustments and changes in treatment, can also be of benefit. 87 If antidepressant medication does not improve symptoms by 4 weeks and adverse effects are tolerable, the initial medication dose should be doubled.…”
Section: How Should Cardiac Patients Be Followed Up After Initiatingmentioning
confidence: 99%